The Effect Of Audio Visual Learning Media Towards Basketball Shooting Outcomes Learning Of SMP Negeri 2 Students At Kawunganten - Mario Dani Pratama; Donny Wira Yudha Kusuma (Indonesian Journal for Physical Education and Sport, 2025)
This study aimed to determine the effect of audio visual learning media towards basketball shooting outcomes among students at SMP Negeri 2 Kawunganten. Using a quantitative experimental approach with a pretest-posttest control group design, the study involved 32 students, divided into an experimental group and control group. The experimental group received audio visual learning media containing basketball shooting techniques, while the control group received traditional learning methods. Data was collected through a basketball shooting test, conducted at a 4 meter distance with 10 shooting attempts. The results were analyzed using descriptive statistics, normality tests, homogeneity test, and an Independent t-test. The findings revealed a significant improvement in the experimental group, with the pre-test average score of 3.36 and post-test average score of 7.00. In contrast, the control group showed a less significant improvement, with a pre-test average score of 3.25 and a post-test average score 4.56. The Independent t-test showed a significant difference in the shooting results between the experimental and control groups (Sig. = 0.001 < 0.05). This indicates that audio visual learning media had a positive effect on improving basketball shooting outcomes. It is concluded that audio visual learning media can significantly enhance basketball shooting skill in students at SMP Negeri 2 Kawunganten.